G17.8 + 16.7: A new supernova remnant - Araya, M.; Hurley-Walker, Natasha; Quirós-Araya, S. (OXFORD UNIV PRESS, 2022)
Non-thermal radio emission is detected in the region of the gamma-ray source FHES J1723.5 - 0501. The emission has an approximately circular shape 0.8° in diameter. The observations confirm its nature as a new supernova remnant, G 17.8 + 16.7. We derive constraints on the source parameters using the radio data and gamma-ray observations of the region. The distance to the object is possibly in the range 1.4-3.5 kpc. An SNR age of the order of 10 kyr is compatible with the radio and GeV features, but an older or younger SNR cannot be ruled out. A simple one-zone leptonic model naturally explains the multi-wavelength non-thermal fluxes of the source at its location outside the Galactic plane.